The shadow teaching scheme for children with autism and attention deficit-hyperactivity disorder in regular classroom - Manansala, Maryola A. (College of Education, University of the Philippines Diliman, 2007)
In the Philippines, the assistantship plan commonly used is the shadow teaching scheme. This study focused on the practice of the shadow teaching scheme for children with autism and attention deficit hyperactivity disorder in regular schools. Information was generated from 15 shadow teachers and 15 regular teachers from 5 schools in Metro Manila. Shadow teachers regard team working the most important task in the shadow teaching scheme followed by managing the mainstreamed child's social and and behavioral skills while least important for them is curriculum planning followed by instruction. For the regular teachers however, curriculum planning is the most important aspect of shadow teaching and teamworking the least. Shadow teachers are advised to master and implement varied teaching strategies.